2011
DOI: 10.1002/jgt.20635
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of b‐Perfect Graphs

Abstract: A b-coloring is a coloring of the vertices of a graph such that each color class contains a vertex that has a neighbor in all other color classes, and the b-chromatic number of a graph G is the largest integer k such that G admits a b-coloring with k colors. A graph is b-perfect if the b-chromatic number is equal to the chromatic number for every induced subgraph of G. We prove that a graph is b-perfect if and only if it does not contain as an induced subgraph a member of a certain list of twenty-two graphs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…More results on Colouring for (H 1 , H 2 )-free graphs can be found in a number of other papers [4,5,11,20,24,28,33,34,36], all of which are summarized in Theorem 3 given below, together with the above results and a weaker formulation of our new result (Statement (ii)-8). In this theorem, the graph C denotes the bull, which is the graph with vertices a, b, c, d, e and edges ab, ac, ad, bc, be and the graph C * 3 denotes the hammer, which is the graph with vertices a, b, c, d, e and edges ab, ac, ad, bc, de.…”
Section: Theorem 2 ([17]mentioning
confidence: 99%
“…More results on Colouring for (H 1 , H 2 )-free graphs can be found in a number of other papers [4,5,11,20,24,28,33,34,36], all of which are summarized in Theorem 3 given below, together with the above results and a weaker formulation of our new result (Statement (ii)-8). In this theorem, the graph C denotes the bull, which is the graph with vertices a, b, c, d, e and edges ab, ac, ad, bc, be and the graph C * 3 denotes the hammer, which is the graph with vertices a, b, c, d, e and edges ab, ac, ad, bc, de.…”
Section: Theorem 2 ([17]mentioning
confidence: 99%
“…Lozin and Malyshev [28] showed that Coloring is polynomial-time solvable for (K 1,3 , 2P 2 )-free graphs. Hoàng, Maffray and Mechebbek [19] characterised the so-called b-perfect graphs in terms of forbidden induced subgraphs and showed that Coloring is polynomial-time solvable for (2P 2 , P 5 )-free graphs. Using their characterisation one can show that (2P 2 , P 5 )-free graphs are b-perfect.…”
Section: Related Workmentioning
confidence: 99%
“…Note that b-perfect graphs are b-monotonous. Recently, Hoang et al have characterized the b-perfect graphs by forbidden subgraphs [13]. For other results on b-coloring one can see [10,7,12] [15] or [9].…”
Section: Introductionmentioning
confidence: 99%